DESIGN OF INTEGRATED PLASTIC WASTE MANAGEMENT BUSINESS MODEL BASED ON DIGITAL CIRCULAR ECONOMY IN CILEGON CITY - Asep Ridwan; Achmad Bahauddin; Dyah Lintang Trenggonowati; Azijul Azhar (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Indonesia is the number two producer of plastic waste. According to Cilegon Mayor Regulation Number 30 of 2019, Article 5 of the Regional Regulation, Cilegon City has a target of reducing waste by 30% and handling waste by 70% of the generation of household waste and waste similar to household waste. One solution is to implement the concept of a circular economy, which is consistent with the five-year master plan data from 2020 to 2024. This research aims to find solutions to problems associated with plastic waste, which is difficult to decompose. An expert opinion, a financial feasibility test using the benefit-cost ratio(BCR) to new revenue streams, and determining the relationship between the circular economy and sustainable development goals were all part of the circular business model canvas (CBMC) used Sustainable Development Goals (SDGs). This research is based on qualitative methods, and quantitative methods are used to test the financial viability of the new revenue stream.Based on the data processing results, it is necessary to redesign using a circular business model canvas, seek product diversification from processing plastic waste, and calculate the feasibility test of the paving block business as a new revenue stream. The current business model canvas was designed as a result of this research. This research is expected to assist IPST Asari and the Bank Sandi Team in maximizing the potential for processing plastic waste in Cilegon City.